Neutrality narratives, gender, and fear of cuckoldry in public administration. (July 2022) - Mastracci, Sharon; Sementelli, Arthur J
Administration draws its legitimacy from neutrality in cultural contexts where power relations are shaped by gendered norms. Neutrality bestows legitimacy where power is vested in the male generative force and is heritable. In the public sphere, neutrality renders administration nonthreatening to politicians and justifies administrators' use of discretion despite their lack of democratic accountability and oversight. We examine historical and cultural roots of administrative neutrality as embodied by the physiologically transformed man and the resulting genderedness of public administration. We highlight two examples of power and sexuality in anime and different implications of neutered maleness. We also discuss enforced administrative neutrality in practice—the Hatch Act in the United States—which prevents administrators from engaging in political activity, rendering them "political eunuchs."